ChemInform Abstract: 3‐Hydrazinoindolin‐2‐one Derivatives: Chemical Classification and Investigation of Their Targets as Anticancer Agents. Issue 43 (7th October 2016) - Ibrahim, Hany S.; Abou‐Seri, Sahar M.; Abdel‐Aziz, Hatem A.
Abstract: Review: 91 refs.